Variation in Leaf Morphological Traits of European Beech and Norway Spruce Over Two Decades in Switzerland - Zhu, Joachim; Thimonier, Anne; Etzold, Sophia; Meusburger, Katrin; Waldner, Peter; Schmitt, Maria; Schleppi, Patrick; Schaub, Marcus; Thormann, Jean-Jacques; Lehmann, Marco M. (Frontiers in Forests and Global Change, 2022)
Leaf morphological traits (LMTs) of forest trees have been observed to vary across space and species. However, long-term records of LMTs are scarce, due to a lack of measurements and systematic leaf archives. This leaves a large gap in our understanding of the temporal dynamics and drivers of LMT variations, which may help us understand tree acclimation strategies. In our study, we used long-term LMT measurements from foliar material collections of European beech (Fagus sylvatica) and Norway spruce (Picea abies), performed every second year from 1995 to 2019 on the same trees within the Swiss Long-term Forest Ecosystem Research Program LWF. The 11 study plots (6 beech, 4 spruce, and 1 mixed) are distributed along gradients of elevation (485–1,650 m a.s.l.), mean annual precipitation (935–2142 mm), and mean annual temperature (3.2–9.8°C). The investigated LMTs were (i) leaf or needle mass, (ii) leaf area or needle length, and (iii) leaf mass per area or needle mass per length. We combined this unique data set with plot variables and long-term data on potential temporal drivers of LMT variations, including meteorological and tree trait data. We used univariate linear regressions and linear mixed-effects models to identify the main spatial and temporal drivers of LMT variations, respectively. For beech LMTs, our temporal analysis revealed effects of mast year and crown defoliation, and legacy effects of vapor pressure deficit and temperature in summer and autumn of the preceding year, but no clear long-term trend was observed. In contrast, spruce LMTs were mainly driven by current-year spring conditions, and only needle mass per length showed a decreasing long-term trend over the study period. In temporal models, we observed that LMTs of both species were influenced by elevation and foliar nutrient concentrations, and this finding was partly confirmed by our spatial analyses. Our results demonstrate the importance of temporal analysis for determining less recognized drivers and legacy effects that influence LMTs, which are difficult to determine across space and species. The observed differences in the temporal drivers of beech and spruce LMTs suggest differences in the adaptation and acclimation potential of the two species.